2013
DOI: 10.9775/kvfd.2012.8196
|View full text |Cite
|
Sign up to set email alerts
|

Quercus infectoria Oliv. ve Achillea millefolium L. Ekstrelerinin Blastocystis spp. İzolatlarına in vitro Etkileri

Abstract: SummaryBlastocystis is a common intestinal parasite that can inhabit the intestinal tract of humans and many animals. Despite it was firstly described almost 100 years ago; many subjects are still under debate about Blastocystis, including its life-cycle, pathogenic potential and treatment of infected individuals. Historically, local plant species have been used for therapeutic purposes by the local people of Anatolia. Here, hexane and methanol extracts of two local plants, Quercus infectoria (Fagaceae) and Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The cytotoxicity of plant extracts with LC 50 value ≤ 20 µg/mL was regarded as a possible cytotoxic plant extract [63]. The results indicated that most plant extracts had low cytotoxicities with considerably high LC 50 value ≥ 100 µg/mL, excluding S. tuberculate (LC 50 = 25.9 µg/mL), D. odorifera (LC 50 = 44.1 µg/mL), I. japonica (LC 50 = 54.1 µg/mL), R. chinensis (LC 50 = 77.6 µg/mL), and Q. infectoria (LC 50 = 91.6 µg/mL), supporting by previous studies that also found a weak cytotoxicity of T. chebula [64,65], S. suberectus [66], Q. infectoria [67,68] and O. indicum [37]. However, it is necessary to test the toxicity by in vivo studies, since in vitro cellular toxicity might provoke different consequences in animals associated with gut interactions and bioavailability of the extracts [18].…”
Section: Cytotoxicity and Safety Of The Tcmp Extractssupporting
confidence: 85%
“…The cytotoxicity of plant extracts with LC 50 value ≤ 20 µg/mL was regarded as a possible cytotoxic plant extract [63]. The results indicated that most plant extracts had low cytotoxicities with considerably high LC 50 value ≥ 100 µg/mL, excluding S. tuberculate (LC 50 = 25.9 µg/mL), D. odorifera (LC 50 = 44.1 µg/mL), I. japonica (LC 50 = 54.1 µg/mL), R. chinensis (LC 50 = 77.6 µg/mL), and Q. infectoria (LC 50 = 91.6 µg/mL), supporting by previous studies that also found a weak cytotoxicity of T. chebula [64,65], S. suberectus [66], Q. infectoria [67,68] and O. indicum [37]. However, it is necessary to test the toxicity by in vivo studies, since in vitro cellular toxicity might provoke different consequences in animals associated with gut interactions and bioavailability of the extracts [18].…”
Section: Cytotoxicity and Safety Of The Tcmp Extractssupporting
confidence: 85%
“…Two of the four articles were conducted in Southeast Asia (Thailand), while the remaining two articles were conducted in Middle East countries (Turkey and Iran) (Table 1). All of the articles reported the use of methanol as a solvent for plant extraction, and two articles reported the use of other solvents such as n-hexane (23, 35) and dichloromethane (23). Nevertheless, the in vitro anti-oxidant and toxicity studies presented in the selected articles were also included in this review to support the efficacies and the anti-parasitic activities of Q. infectoria .…”
Section: Resultsmentioning
confidence: 99%
“…A total of three in vitro anti-parasitic studies were conducted by Sawangjaroen and Sawangjaroen (23), Ozbilgin et al (35) and Kheirandish et al (36), while two in vivo studies were carried out by Sawangjaroen et al (37) and Kheirandish et al (36) (Table 4). Three types of parasites were subjected to the studies: Entamoeba histolytica (37), Blastocystis hominis and Blastocystis spp (23, 35) and Leishmania major (36). For the in vivo studies, mice models were exclusively used, specifically female Swiss albino mice and male BALB/c mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations